KAJIAN KARBONASI PADA BETON MUTU TINGGI MEMADAT MANDIRI DENGAN VARIASI KOMPOSISI METAKAOLIN - Wibowo Wibowo; Endah Safitri; Delista Putri Deni (Civil Engineering Study Program, Engineering Faculty Universitas Sebelas Maret, 2020)
The construction industry is an important thing to support the development of a country. In concrete construction, quality, strength, and durability of concrete are the main requirements of all. In urban tropical countries, carbonation is one of the essential factors that affect the durability of concrete, and it may cause corrosion of reinforced steel in concrete. Therefore, high strength self-compacting concrete may be expected as the solution, improved by pozzolanic additions, metakaolin with substitution dosage at 10%; 12,5%; 15%; 17,5%; and 20%. This study purposed to determine the effect of metakaolin and its optimum dosage to improve high strength self-compacting concrete quality on its carbonation rates. This study was done by using experimental methods. It needs a plain cylindrical concrete with 75 mm diameter and 150 mm height, and testing by SNI 03-6468-2000, EFNARC 2002, and SEM-PUPR 25-2015. The carbonation test is done using accelerated laboratory carbonation in Structures and Materials Laboratory, Faculty of Engineering, Universitas Sebelas Maret by soaking the specimens in a 4% carbonate solution for 15 days, 37 days, and 51 days, proceeded by splitting using CTM, and spray it using a 1% phenolphthalein indicator to determine its carbonation depth. Based on the results, metakaolin might improve concrete quality by reducing its carbonation rates by 15% substitution dosage of cement content, with a nominal atmospheric carbonation coefficient 3,71 mm/year½, reduced 44,41% from HSSCC without metakaolin substitution. Metakaolin addition might reduce fresh concrete's workability and fulfill self-compacting concrete requirements specified by EFNARC 2002.